Processamento, caracterização microestrutural e avaliação das propriedades mecanicas da liga Al92Fe3Cr2Mn3 - Pereira, Hudson Henrique (2008)
Aluminum alloys having a particle dispersion in nanometric scale, which present elevated values of mechanical strength at both ambient and high temperatures have been studied for some time. These alloys are known for presenting icosahedral particles embedded in an α-Al matrix and they are called nanoquasicrystalline alloys, having large thermal stability as their major characteristic. The present work aims to evaluate the mechanical properties and the possibility of formation of quasicrystalline phases in an Al92Fe3Cr2Mn3 rapidly solidified to produce bulk samples. The alloy was characterized by scanning electron microscopy (SEM), X-ray diffraction (DRX) and differential scanning calorimetry (DSC). The mechanical properties were evaluated by compression tests at ambient and high temperatures and also by microhardness tests. The results showed refined microstructure and possibility of presence of quasicrystalline phase. Elevated mechanical strength was observed for the alloy even in temperatures up to 300°C, always associated with good plasticity in compression.